Forming a Government in the Event of a Hung Parliament : The UK's Recognition Rules in Comparative Context /: The UK's Recognition Rules in Comparative Context. (May 2016) - Schleiter, Petra; Belu, Valerie; Hazell, Robert
No abstract available